Coating composition, coating, and preparation method and application of coating
By using highly adsorption coating compositions in the LPCVD process, the erosion and process pollution of the polysilicon layer on metal parts is solved, and a longer service life and a more stable process is achieved.
Patent Information
- Application Number
- CN202411292446.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-27
AI Technical Summary
In the LPCVD process, the deposition of the polysilicon layer causes a large amount of polysilicon layer to be deposited on the air intake pipe and the surface of the metal heat insulation plate, causing serious erosion and process pollution, and reducing the service life of the parts.
Using a coating composition, including 50% to 90% by weight of composite filler and 5% to 30% by weight of silicon carbide, a coating with strong adsorption is formed by sintering, thereby increasing the binding force between the polycrystalline silicon and the metal matrix, and reducing the fall of the polycrystalline silicon. risk.
Effectively isolate the direct contact between polysilicon and metal matrix, reduce the risk of corrosion, improve the heat resistance, oxidation resistance and corrosion resistance of the coating, extend the service life of metal parts, and reduce process pollution.
Smart Images

Figure CN119192884A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of coating technology, and in particular to a coating composition, a coating, a coating preparation method and an application. Background Art
[0002] The core process of TOPCon solar cell processing is the process of making tunnel oxide layer and polysilicon layer. The preparation methods of the above two film layers can be divided into low pressure chemical vapor deposition (LPCVD), plasma enhanced chemical vapor deposition (PECVD) and physical vapor deposition (PVD). The LPCVD process uses LPCVD equipment to grow silicon oxide layer and deposit polysilicon by thermal oxidation.
[0003] LPCVD is one of the important processes for depositing α-Si / polysilicon layers under low pressure conditions. In this process, since the process gas required for the reaction needs to be introduced into the furnace tube during the deposition process, the gas needs to be transported to the corresponding position of the furnace tube through the air inlet pipe, which is usually made of metal; in addition, since the gas reaction requires a high temperature environment, the furnace door needs to be sealed, and there will be a large temperature difference when entering and leaving the boat, so a certain number of metal insulation sheets are usually placed near the furnace tube mouth to prevent the heat in the furnace from directly impacting the outside and blocking a certain amount of heat. However, since the process gas will react to deposit polysilicon in the furnace tube, a large amount of polysilicon layer will be deposited on the surface of the air inlet pipe and the metal insulation board. The polysilicon layer will cause serious erosion to metal materials such as the air inlet pipe and the metal insulation board, resulting in failure of parts, reducing the service life of parts and increasing costs. In addition, the polysilicon layer attached to the surface of the air inlet pipe and the metal insulation board is easy to fall off, causing process pollution. In addition to the air intake pipe and heat insulation sheet, other components such as metal furnace tubes, flow equalizer barrels, and flow equalizer plates may also have the above problems. Summary of the invention
[0004] In view of this, in order to solve at least one of the above defects, it is necessary to propose a coating composition and a coating formed by the coating composition, which has strong adsorption properties, can improve the bonding strength between the substrate and the deposited polysilicon, and effectively reduce the risk of polysilicon falling off.
[0005] In addition, the present application also provides a method for preparing the aforementioned coating and a coating device for the coating.
[0006] An embodiment of the present application provides a coating composition, comprising: 50wt% to 90wt% of a composite filler and 5wt% to 30wt% of silicon carbide, wherein the composite filler is formed by sintering a filler raw material, and the filler raw material comprises: the filler raw material comprises: silicon dioxide, aluminum oxide, component A, component B and component C, the component A comprises at least one of boron oxide, sodium oxide and potassium oxide, the component B comprises at least one of calcium oxide, magnesium oxide and zirconium oxide, and the component C comprises at least one of nickel oxide and cobalt oxide.
[0007] In some possible embodiments, the filler material includes:
[0008] 30wt% to 90wt% silicon dioxide;
[0009] 1wt% to 30wt% alumina;
[0010] At least one of 0.3 wt% to 10 wt% boron oxide, 1 wt% to 20 wt% sodium oxide, and 1 wt% to 20 wt% potassium oxide;
[0011] at least one of 1 wt% to 10 wt% calcium oxide, 1 wt% to 10 wt% magnesium oxide, and 1 wt% to 10 wt% zirconium oxide; and
[0012] At least one of 1 wt% to 15 wt% nickel oxide and 1 wt% to 15 wt% cobalt oxide.
[0013] In some possible embodiments, the average particle size of the composite filler is 10 μm to 150 μm.
[0014] In some possible embodiments, the coating composition further includes: 1wt% to 10wt% of a dispersant and 1wt% to 10wt% of a film-forming agent, wherein the dispersant includes at least one of sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate; and the film-forming agent includes at least one of sodium carboxymethyl cellulose, microcrystalline cellulose and hydroxypropyl cellulose.
[0015] The embodiment of the present application also provides a coating, which is formed by curing the coating composition as described above.
[0016] The present application also provides a method for preparing a coating, the method comprising:
[0017] The filler raw material is sintered for the first time, and the sintered product is ground to obtain a composite filler, wherein the filler raw material includes: silicon dioxide, aluminum oxide, component A, component B and component C, the component A includes at least one of boron oxide, sodium oxide and potassium oxide, the component B includes at least one of calcium oxide, magnesium oxide and zirconium oxide, and the component C includes at least one of nickel oxide and cobalt oxide;
[0018] Mixing 50 wt% to 90 wt% of a composite filler with 5 wt% to 30 wt% of silicon carbide to form a coating composition; and
[0019] The coating composition is applied to the surface of the metal substrate to form a film layer, and then the coating layer is formed through a second sintering.
[0020] In some possible embodiments, the first sintering temperature is 1000° C. to 1400° C., and the time is 10 min to 60 min; and / or the grinding includes ball milling, and the rotation speed of the ball mill is 200 to 400 r / min, and the time is 5 to 24 h.
[0021] In some possible embodiments, the second sintering temperature is 600° C. to 900° C., and the time is 20 min to 60 min; and / or the coating is performed by spraying, the spraying pressure is 0.3 to 0.6 MPa, and the spraying distance is 15 to 45 cm.
[0022] In some possible embodiments, the filler material includes:
[0023] 30wt% to 90wt% silicon dioxide;
[0024] 1wt% to 30wt% alumina;
[0025] At least one of 0.3 wt% to 10 wt% boron oxide, 1 wt% to 20 wt% sodium oxide, and 1 wt% to 20 wt% potassium oxide;
[0026] at least one of 1 wt% to 10 wt% calcium oxide, 1 wt% to 10 wt% magnesium oxide, and 1 wt% to 10 wt% zirconium oxide; and
[0027] At least one of 1wt% to 15wt% nickel oxide and 1wt% to 15wt% cobalt oxide;
[0028] The step of forming the coating composition also includes: adding 1wt% to 10wt% of a dispersant and 1wt% to 10wt% of a film-forming agent, wherein the dispersant includes at least one of sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate; and the film-forming agent includes at least one of sodium carboxymethyl cellulose, microcrystalline cellulose and hydroxypropyl cellulose.
[0029] An embodiment of the present application also provides a coating device, which includes a heating device and a metal component arranged in the heating device, wherein the metal component has a coating, and the coating is the coating as described above or a coating obtained by the coating preparation method described above.
[0030] The coating formed by the coating composition of the embodiment of the present application has high temperature resistance, oxidation resistance, corrosion resistance and strong adsorption, and the coating has a high hardness, which can effectively isolate the metal substrate from the polysilicon and improve the metal substrate's resistance to polysilicon erosion; at the same time, the strong adsorption of the coating can effectively adsorb polysilicon, improve the bonding force between the polysilicon layer and the coating, and reduce the risk of polysilicon falling off. Therefore, the coating of the present application can achieve the premise of blocking direct contact between polysilicon and the metal substrate, and can further reduce the process pollution in the polysilicon film forming cavity caused by the falling of polysilicon. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A flow chart of a method for preparing a highly adsorbent coating provided in one embodiment of the present application.
[0032] Figure 2 This is a metallographic microscope photograph of polycrystalline silicon adsorbed on the surface of an uncoated metal heat shield.
[0033] Figure 3 This is a metallographic microscope photograph of the metal substrate and coating of Example 1 of the present application.
[0034] Figure 4 This is a real photo of the coating formed on the separator in Example 1 of the present application.
[0035] The following specific implementation manner will further illustrate the embodiments of the present application in conjunction with the above-mentioned drawings. DETAILED DESCRIPTION
[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the technical field belonging to the embodiments of the present application. The terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the embodiments of the present application. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the raw materials, reagents or instruments used do not specify the manufacturer, they are all conventional products that can be purchased commercially.
[0037] It should be noted that all directional indications in the embodiments of the present application (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0038] It will be understood that when a layer is referred to as being "on" another layer, it can be directly on the other layer or intervening layers may be present therebetween. Conversely, when a layer is referred to as being "directly on" another layer, there are no intervening layers. When a component is referred to as being "fixed to," "mounted to," or "disposed on" another component, it can be directly on the other component or an intervening component may also be present.
[0039] Here, the embodiments of the present application are described with reference to the cross-sectional views, which are schematic diagrams of the idealized embodiments (and intermediate configurations) of the present application. Thus, it is foreseeable that the shapes of the diagrams are different due to manufacturing processes and / or tolerances. Therefore, the embodiments of the present application should not be interpreted as being limited to the specific shapes of the regions illustrated here, but should include deviations in shapes such as those produced due to manufacturing. The regions shown in the figures are themselves only schematic, and their shapes are not intended to illustrate the actual shapes of the devices, and are not intended to limit the scope of the present application.
[0040] Some embodiments of the present application are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0041] The low-pressure chemical vapor deposition (LPCVD) process is one of the important processes for depositing α-Si / polysilicon layers under low-pressure conditions. In this process, the reaction of depositing polysilicon often occurs, resulting in a large amount of polysilicon layer deposited on the surface of metal parts such as the intake pipe and metal heat shield, which will cause serious erosion to the intake pipe and metal heat shield; in addition, the shedding of the polysilicon layer attached to the surface of the metal parts will also cause contamination in the process.
[0042] To this end, the embodiment of the present application forms a coating on the surface of the metal parts. On the one hand, the coating can play a role of isolation and protection, avoiding direct contact between polysilicon and metal parts, and reducing the risk of polysilicon erosion of metal parts. On the other hand, the coating has strong adsorption properties and can achieve strong adsorption of polysilicon particles. The risk of polysilicon deposited on the surface of metal parts falling off is low, thereby reducing process pollution caused by the falling off of polysilicon.
[0043] The coating provided in the embodiment of the present application is formed by curing a coating composition, which comprises: 50wt% to 90wt% of a composite filler and 5wt% to 30wt% of silicon carbide. The composite filler is formed by sintering a filler raw material. The filler raw material comprises: silicon dioxide, aluminum oxide, component A, component B and component C, wherein component A comprises at least one of boron oxide, sodium oxide and potassium oxide, component B comprises at least one of calcium oxide, magnesium oxide and zirconium oxide, and component C comprises at least one of nickel oxide and cobalt oxide.
[0044] In addition, the coating composition may further include 1 wt% to 10 wt% of a dispersant and 1 wt% to 10 wt% of a film former to facilitate the dispersion of the composite filler and the film formation of the coating composition.
[0045] By subjecting the above filler raw materials to high temperature sintering, in the early stage, the film-forming agent (sodium carboxymethyl cellulose, microcrystalline cellulose and hydroxypropyl cellulose, etc.) is solidified into a film, and the ceramic particle filler (i.e., composite filler) is tightly bonded. As the temperature rises, the viscosity of the film-forming agent increases, and it shrinks, and the ceramic particles are further gathered together, and the gaps between the ceramic particles are reduced, which is conducive to subsequent firing. When the temperature continues to rise, the film-forming agent volatilizes into water and carbon dioxide to escape, and the powder particles are fired into a space network structure with Si-O bonds as the main body. This structure has a dense surface, softens at high temperatures, and has increased viscosity, and is very easy to adsorb gas and fine particles. However, if only the Si-O structure is used to directly adsorb the silicon deposited by LPCVD, this structure is prone to collapse. For this reason, components such as silicon carbide and zirconium oxide are added in the embodiment of the present application. Since zirconium dioxide is distributed at the fulcrum of the space network structure, silicon carbide is distributed at the periphery of the network structure, which increases the stability of the network structure, so that the formed Si-O structure adsorbs crystalline silicon without collapse. Transition metal elements are introduced, which have good bonding with the metal matrix, so that the coating can withstand thermal stress and silicon production stress without falling off.
[0046] Silicon dioxide (SiO2) as the main body of the composite filler has a great influence on the structure of the composite filler, and can form a Si-O spatial network structure. In some embodiments, the addition amount of SiO2 is 30wt% to 90wt%, and further can be 60wt% to 90wt%. When the addition amount is too low, the spatial network structure cannot be formed and the film cannot be formed. When the addition amount is too high, other functional substances are reduced and cannot effectively adsorb and block the erosion of silicon.
[0047] Alumina (Al2O3) can promote the formation of a network structure of Si-O bonds. Al-O bonds cooperate with Si-O bonds to form many continuous skeletons that are combined with each other, thereby improving the temperature resistance of the network structure. In some embodiments, the addition amount of Al2O3 is 1wt% to 30wt%, and can further be 3wt% to 15wt%. When the addition amount is too low, the formed coating film is not dense enough. When the addition amount is too high, the formed coating film will have excessive internal stress and crack.
[0048] Boron oxide (B2O3) has similar effects to aluminum oxide and can also be used as a flux because of its low melting point. In some embodiments, the amount of B2O3 added is 0.3 wt% to 10 wt%, and further can be 0.5 wt% to 5 wt%.
[0049] Nickel oxide (NiO) and cobalt oxide (CoO) are transition metal oxides, which have good bonding properties with metals such as iron (Fe), can be used as binders, and can form metallurgical bonds with metals such as iron at high temperatures. In some embodiments, the amount of nickel oxide added is 1wt% to 15wt%, and can further be 1wt% to 10wt%, and the amount of cobalt oxide added is 1wt% to 15wt%, and can further be 1wt% to 10wt%. When the amount of transition metal oxide added is too low, the bonding force is reduced, and when the amount added is too high, the internal stress generated by the bonding is too large, which may cause the film to crack.
[0050] Zirconia (ZrO2) ceramics are resistant to acid and alkali, and resistant to silicon corrosion. Zirconia is evenly dispersed in the Si-O (Al-O / BO) spatial network structure, and it can effectively resist silicon corrosion caused by the LPCVD process. In some embodiments, the addition amount of zirconium oxide is 1wt% to 10wt%, and can further be 1wt% to 5wt%.
[0051] The above components may also contain alkali metal oxides, which have a low melting point and can accelerate the breaking of structural bonds of other high melting point substances, promote the formation of low melting point eutectics, and are conducive to firing into a dense spatial network structure. In some embodiments, the alkali metal oxides may include sodium oxide and potassium oxide, etc. In some embodiments, the content of sodium oxide (Na2O) may be 1wt% to 20wt%, and further may be 1wt% to 10wt%. The content of potassium oxide (K2O) may be 1wt% to 20wt%, and further may be 1wt% to 10wt%.
[0052] The above components may also contain alkaline earth metal oxides, such as magnesium oxide and calcium oxide. The thermal expansion coefficient of MgO is close to that of the metal matrix, which is about 12.8×10 -6 / ℃~14.4×10 -6 / ℃, the thermal expansion coefficient of 304 stainless steel is about 18.4×10 -6 / ℃, MgO can adjust the thermal expansion coefficient of the coating, further improve the bonding strength between the coating and the metal substrate, and further improve the stability of the coating. CaO can not only further improve the stability of the coating, but also act as a certain flux. In some embodiments, the content of calcium oxide (CaO) can be 1wt% to 10wt%, and further can be 1wt% to 5wt%. The content of magnesium oxide (MgO) can be 1wt% to 10wt%, and further can be 1wt% to 5wt%.
[0053] In some embodiments, the average particle size of the composite filler may be 10 μm to 150 μm. By adjusting the particle size of the composite filler, the dispersion uniformity of the composite filler and the thickness uniformity of the formed coating can be improved.
[0054] The thermal conductivity of silicon carbide is about 270W / (m·K), which is a good thermal conductive material. In addition, silicon carbide is stable at high temperatures and does not react with silicon deposited in LPCVD. When the coating is heated at high temperature, silicon carbide has good thermal conductivity and is evenly dispersed throughout the space of the coating. It can quickly conduct heat from the proximal end to the distal end, so that the coating is heated evenly and avoids thermal stress concentration that causes the coating to crack. In addition, silicon carbide is stable in nature and can effectively prevent silicon from corroding the metal substrate. When the amount of silicon carbide added is too low, the stability of the coating will be reduced. When the amount added is too high, the stress in the coating will be excessive and there may be a risk of cracking.
[0055] The dispersant may include at least one of sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, etc. By adding a proper amount of the dispersant, the dispersibility of the composite filler can be improved.
[0056] The film-forming agent may include at least one of sodium carboxymethyl cellulose, microcrystalline cellulose, hydroxypropyl cellulose, etc. By adding an appropriate amount of the film-forming agent, the early film-forming property of the coating composition can be improved to facilitate the preparation of the coating. After the coating system is sintered at a high temperature, the inorganic substance forms a dense network structure to form a film.
[0057] By sintering the aforementioned filler raw materials at high temperature to form a eutectic spatial network structure, and grinding to form a granular composite filler, the composite filler has good volume stability and a moderate elastic modulus, and can effectively improve the hardness of the formed coating, and improve the scratch resistance and wear resistance of the coating. By forming a coating composition with the aforementioned composite filler and silicon carbide, it is mainly applied to the surface of a metal substrate, and solidified to form a coating with strong adsorption, which can effectively improve the heat resistance, corrosion resistance, wear resistance, etc. of the coating, isolate the direct contact between the metal substrate and polysilicon, so that the formed coating has good high temperature protection, and improves the polysilicon corrosion resistance of metal parts. In addition, when polysilicon film is produced by low-pressure chemical vapor deposition (LPCVD), the highly adsorbent coating will have a small amount of molten material in a high-temperature environment, the entire coating surface softens, and the viscosity increases, which can achieve a more reliable bonding to the deposited polysilicon, which is equivalent to improving the adsorption of the coating to polysilicon, and can firmly adsorb the polysilicon particles to the surface of the coating to reduce process pollution caused by polysilicon shedding; therefore, a longer period of polysilicon deposition can be achieved, the service life of the metal substrate can be extended, and the normal replacement cycle can be met, thereby ensuring the process stability within the cycle.
[0058] See also Figure 1 Based on the same inventive concept, the present application also provides a method for preparing the aforementioned coating, and the preparation method specifically comprises the following steps:
[0059] Step S1, sintering the filler raw material for the first time, and grinding the sintered product to obtain a composite filler, wherein the filler raw material includes: silicon dioxide, aluminum oxide, component A, component B and component C, the component A includes at least one of boron oxide, sodium oxide and potassium oxide, the component B includes at least one of calcium oxide, magnesium oxide and zirconium oxide, and the component C includes at least one of nickel oxide and cobalt oxide.
[0060] In some embodiments, the filler raw material includes: 30wt% to 90wt% silica; 1wt% to 30wt% alumina; at least one of 0.3wt% to 10wt% boron oxide, 1wt% to 20wt% sodium oxide and 1wt% to 20wt% potassium oxide; at least one of 1wt% to 10wt% calcium oxide, 1wt% to 10wt% magnesium oxide and 1wt% to 10wt% zirconium oxide; at least one of 1wt% to 15wt% nickel oxide and 1wt% to 15wt% cobalt oxide.
[0061] In some embodiments, the first sintering is performed at a temperature of 1000° C. to 1400° C. and for a time of 10 min to 60 min.
[0062] In some embodiments, the grinding method of the sintered product includes ball milling, and the rotation speed of the ball mill is 200-400 r / min and the time is 5-24 h.
[0063] In some embodiments, the average particle size of the composite filler is 10 μm to 150 μm.
[0064] Specifically, alcohol is added to the weighed raw material mixture and ball-milled for 1 to 10 hours at a rotation speed of 200 to 400 r / min; the obtained slurry is dried at 100°C for 12 hours to obtain a dried powder; the dried powder is sintered in a high-temperature furnace at 1000°C to 1400°C for 5 to 24 hours, the melt is water-cooled, and alcohol is added to the solid sintered product obtained by water cooling, and ball-milled for 5 to 24 hours at a rotation speed of 200 to 400 r / min to obtain a composite filler.
[0065] Step S2, mixing 50 wt% to 90 wt% of the composite filler with 5 wt% to 30 wt% of silicon carbide to form a coating composition.
[0066] Specifically, 30 wt% to 100 wt% of the total amount of distilled water is added to the mixture, and the mixture is dispersed at a speed of 200 to 600 r / min for 30 to 120 minutes to uniformly disperse the particulate matter in the mixture.
[0067] In some embodiments, step S2 further includes: adding 1 wt% to 10 wt% of a dispersant and 1 wt% to 10 wt% of a film-forming agent.
[0068] In some embodiments, the dispersant may include at least one of sodium tripolyphosphate, sodium metaphosphate, sodium pyrophosphate, etc. By adding a proper amount of the dispersant, the dispersibility of the composite filler may be improved.
[0069] In some embodiments, the film-forming agent may include at least one of sodium carboxymethyl cellulose, microcrystalline cellulose, hydroxypropyl cellulose, etc. By adding an appropriate amount of the film-forming agent, the early film-forming property of the coating composition can be improved.
[0070] Step S3, coating the coating composition on the surface of the metal substrate to form a film layer, and then sintering for the second time to form a coating with strong adsorption.
[0071] Specifically, the coating composition is air-sprayed onto the surface of the metal substrate at a spraying pressure of 0.3-0.6 MPa and a spraying distance of 15-45 cm. After natural drying, the coating composition is sintered for a second time at 600-900° C. for 20-60 min, and then cooled to obtain a highly adsorbent coating.
[0072] The coating preparation method of the embodiment of the present application is low-cost and suitable for large metal substrates and large-area coating preparation. It has almost no special requirements for the preparation environment and can realize coating preparation operations in a variety of scenarios.
[0073] The metal parts coating solution provided in the embodiment of the present application has lower preparation cost and no restrictions on the preparation environment compared to PVD and CVD solutions. It is a brand-new technical solution for metal parts deposited by LPCVD in the TOPCon process to resist polysilicon corrosion and prevent process pollution. Moreover, it can meet all-weather, low-restriction coating processing, achieve low-cost coating spraying and sintering, and has a simple process and strong applicability. It can realize the surface coating preparation of large parts, complex structural parts, and special-shaped parts. In addition, the coating solution of this embodiment realizes the preparation of the coating on the basis of existing metal parts, thereby achieving the effect of corrosion resistance. Therefore, there is no need to replace or develop new materials, and the cost is low and the applicability is strong.
[0074] The embodiments of the present application are further described below through specific examples.
[0075] Embodiment 1:
[0076] (1) 80 wt% silicon dioxide, 10 wt% aluminum oxide, 2 wt% zirconium oxide, 1 wt% boron oxide, 1 wt% sodium oxide, 1 wt% potassium oxide, 1 wt% calcium oxide, 1 wt% magnesium oxide, 1 wt% cobalt oxide, and 2 wt% nickel oxide powders are mixed, and alcohol is added and ball-milled for 1 to 10 hours at a speed of 300 r / min; the resulting slurry is dried at 100°C for 12 hours to obtain a dried powder; the dried powder is sintered in a high-temperature furnace at 1300°C for 40 minutes, the melt is water-cooled, and the water-cooled solid is added with alcohol and ball-milled for 12 hours at a speed of 300 r / min to obtain a composite filler (i.e., the first component).
[0077] (2) Add 60 wt % of distilled water to 90 wt % of the first component, 5 wt % of SiC, 2 wt % of sodium tripolyphosphate and 3 wt % of sodium carboxymethyl cellulose, and disperse at 400 r / min for 30 to 120 min to obtain a coating composition (i.e., the second component).
[0078] (3) The second component is air-sprayed onto the surface of the metal part at a spraying pressure of 0.5 MPa and a spraying distance of 30 cm. The metal part is then naturally dried and hot-fired at 700°C for 45 minutes. The strong adsorption coating is obtained by cooling the metal part.
[0079] Embodiment 2:
[0080] The difference from Example 1 is that the sintering temperature in step (3) is 600° C. For the rest, please refer to Example 1 for details.
[0081] Embodiment 3:
[0082] The difference from Example 1 is that the sintering temperature in step (3) is 800° C. For the rest, please refer to Example 1 for details.
[0083] Embodiment 4:
[0084] (1) A mixture of 80 wt% silicon dioxide, 10 wt% aluminum oxide, 3 wt% zirconium oxide, 1 wt% boron oxide, 1 wt% sodium oxide, 1 wt% potassium oxide, 1 wt% calcium oxide, 1 wt% magnesium oxide, 1 wt% cobalt oxide, and 1 wt% nickel oxide is added with alcohol and ball-milled for 1 to 10 hours at a speed of 300 r / min; the resulting slurry is dried at 100° C. for 12 hours to obtain a dried powder; the dried powder is kept at 1300° C. in a high-temperature furnace for 40 minutes, the melt is water-cooled, and the water-cooled solid is ball-milled with alcohol for 12 hours at a speed of 300 r / min to obtain a first component.
[0085] (2) Add 60 wt % of distilled water to 90 wt % of the first component, 5 wt % of SiC, 2 wt % of sodium tripolyphosphate, and 3 wt % of sodium carboxymethyl cellulose, and disperse at 400 r / min for 30 to 120 min to obtain a second component.
[0086] (3) The second component is air-sprayed onto the surface of the metal part at a spraying pressure of 0.5 MPa and a spraying distance of 30 cm. The metal part is then naturally dried and then hot-fired at 700°C for 45 minutes to obtain a highly adsorbent coating.
[0087] Embodiment 5:
[0088] The difference from Example 4 is that the second component is selected from 85wt% of the first component, 10wt% of SiC, 2wt% of sodium tripolyphosphate, and 3wt% of sodium carboxymethyl cellulose. Please refer to Example 4 for the rest.
[0089] Embodiment 6:
[0090] The difference from Example 4 is that the second component is 80wt% of the first component, 15wt% of SiC, 2wt% of sodium tripolyphosphate, and 3wt% of sodium carboxymethyl cellulose. Please refer to Example 4 for the rest.
[0091] Embodiment 7:
[0092] (1) 80 wt% silicon dioxide, 10 wt% aluminum oxide, 3 wt% zirconium oxide, 1 wt% boron oxide, 1 wt% sodium oxide, 1 wt% potassium oxide, 1 wt% calcium oxide, 1 wt% magnesium oxide, 1 wt% cobalt oxide, and 1 wt% nickel oxide powders are mixed, alcohol is added, and the mixture is ball-milled for 1 to 10 hours at a speed of 300 r / min; the resulting slurry is dried at 100° C. for 12 hours to obtain a dried powder; the dried powder is kept in a high-temperature furnace at 1300° C. for 40 minutes, the melt is water-cooled, and the water-cooled solid is ball-milled with alcohol for 12 hours at a speed of 300 r / min to obtain a first component.
[0093] (2) Add 60 wt % of distilled water to 90 wt % of the first component, 5 wt % of SiC, 2.5 wt % of sodium tripolyphosphate, and 2.5 wt % of sodium carboxymethyl cellulose, and disperse at 400 r / min for 30 to 120 min to obtain a second component.
[0094] (3) The second component is air-sprayed onto the surface of the metal part at a spraying pressure of 0.5 MPa and a spraying distance of 30 cm. The metal part is then naturally dried and hot-fired at 700°C for 45 minutes. The strong adsorption coating is obtained by cooling the metal part.
[0095] Embodiment 8:
[0096] The difference from Example 7 is that the second component selects 90wt% of the first component, 5wt% of SiC, 1wt% of sodium tripolyphosphate, and 4wt% of sodium carboxymethyl cellulose. Please refer to Example 7 for the rest.
[0097] Embodiment 9:
[0098] The difference from Example 7 is that the second component is selected from 90wt% of the first component, 5wt% of SiC, 4wt% of sodium tripolyphosphate, and 1wt% of sodium carboxymethyl cellulose. Please refer to Example 7 for the rest.
[0099] Comparative Example 1
[0100] The LPCVD equipment directly uses metal heat shields without coating.
[0101] like Figure 2 As shown, it is a metallographic microscope photo of the metal heat shield (i.e., metal substrate) in the LPCVD device in Comparative Example 1 without a coating. Figure 2 It can be seen that after the polysilicon grows to the heat insulation sheet, the polysilicon causes corrosion to the substrate of the metal heat insulation sheet.
[0102] like Figure 3 The figure shows the metallographic microscope photos of the metal substrate and the coating after the metal substrate with the coating in Example 1 is applied to the LPCVD equipment. Figure 3 It can be seen that there is no obvious interface between the metal substrate and the coating, indicating that the coating can stably adhere to the surface of the metal substrate and exhibit strong binding force. In addition, a large number of polysilicon particles are adsorbed on the surface of the coating, indicating that the coating with strong adsorption can firmly adsorb polysilicon.
[0103] like Figure 4 The figure is a real photo of the surface of the metal heat shield in the LPCVD equipment having the above-mentioned coating formed thereon. Figure 4 It can be seen that the aforementioned coating composition has good film-forming property and the formed coating surface has high quality.
[0104] The corresponding test data of Examples 1 to 9 are shown in Table 1.
[0105] Table 1
[0106]
[0107] Adhesion test method: pull-off method, the instrument is KS-M coating adhesion tester.
[0108] Thermal shock stability test method: Heat the sample to 800°C, then take out the sample and cool it to room temperature in air, and repeat this cycle.
[0109] Salt spray resistance test: 5% NaCl salt spray test.
[0110] Coating thickness test method: The coating thickness is measured using the Hall effect and eddy current effect. The measuring instrument is the Linshang LS221 coating thickness gauge.
[0111] It can be seen from Examples 1 to 3 that the metal substrate with a strongly adsorbent coating attached thereto has a much longer salt spray resistance test time than the bare metal substrate, and the coating adhesion and 600°C water-cooled thermal shock stability are both good, especially Example 1, which performs more prominently. This is mainly because the second sintering temperature of 700°C is more conducive to improving the adhesion and thermal shock stability of the coating.
[0112] It can be seen from Examples 4 to 6 that the metal substrate after forming the coating has a much longer salt spray resistance test time than the bare metal substrate, and the coating adhesion and thermal shock stability are good, especially Example 4. This is mainly because in Example 4, by regulating the content of zirconium oxide and nickel oxide components in the first component, as well as the content of silicon carbide components in the first component, the adhesion and thermal shock stability of the coating can be effectively improved.
[0113] It can be seen from Examples 7 to 9 that the metal substrate with a strongly adsorbent coating has a much longer salt spray resistance than the bare metal substrate, and the coating has good adhesion and 600°C water-cooled thermal shock stability.
[0114] It can be seen that the strong adsorption coating of Examples 1-9 of the present application can achieve the barrier between polysilicon and the metal substrate, avoid direct contact between polysilicon and the metal substrate, and slow down the erosion of the metal substrate by polysilicon. In addition, during the process of polysilicon deposition, under high temperature conditions, such coatings will form molten substances, which can show strong adsorption and achieve a more reliable bonding force to the deposited polysilicon, which is equivalent to improving the adsorption of the coating to the polysilicon, reducing the shedding of polysilicon, and reducing the occurrence of process pollution. In this case, a longer period of polysilicon deposition can be achieved, the service life of metal parts can be extended, and the normal replacement cycle can be met, thereby ensuring the process stability within the cycle.
[0115] The above descriptions are some specific implementations of the present application, but they are not limited to these implementations in actual application. For ordinary technicians in this field, other variations and changes made according to the technical concept of the present application should all fall within the protection scope of the present application.
Claims
1. A coating composition, characterized in that include: 50wt% to 90wt% of a composite filler and 5wt% to 30wt% of silicon carbide, wherein the composite filler is formed by sintering a filler raw material, and the filler raw material includes: silicon dioxide, aluminum oxide, component A, component B and component C, the component A includes at least one of boron oxide, sodium oxide and potassium oxide, the component B includes at least one of calcium oxide, magnesium oxide and zirconium oxide, and the component C includes at least one of nickel oxide and cobalt oxide.
2. The coating composition according to claim 1, characterized in that The filler raw materials include: 30wt% to 90wt% silicon dioxide; 1wt% to 30wt% alumina; At least one of 0.3 wt% to 10 wt% boron oxide, 1 wt% to 20 wt% sodium oxide, and 1 wt% to 20 wt% potassium oxide; at least one of 1 wt% to 10 wt% calcium oxide, 1 wt% to 10 wt% magnesium oxide, and 1 wt% to 10 wt% zirconium oxide; and At least one of 1 wt% to 15 wt% nickel oxide and 1 wt% to 15 wt% cobalt oxide.
3. The coating composition according to claim 1, characterized in that The average particle size of the composite filler is 10 μm to 150 μm.
4. The coating composition according to claim 1, characterized in that Also includes: 1 wt% to 10 wt% of a dispersant and 1 wt% to 10 wt% of a film-forming agent, The dispersant includes at least one of sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate; The film-forming agent includes at least one of sodium carboxymethyl cellulose, microcrystalline cellulose and hydroxypropyl cellulose.
5. A coating, characterized in that: The coating layer is formed by curing the coating composition according to any one of claims 1 to 4.
6. A method for preparing a coating, characterized in that: include: The filler raw material is first sintered, and the sintered product is ground to obtain a composite filler, wherein the filler raw material comprises: silicon dioxide, aluminum oxide, component A, component B and component C, the component A comprises at least one of boron oxide, sodium oxide and potassium oxide, the component B comprises at least one of calcium oxide, magnesium oxide and zirconium oxide, and the component C comprises at least one of nickel oxide and cobalt oxide; Mixing 50 wt% to 90 wt% of the composite filler with 5 wt% to 30 wt% of silicon carbide to form a coating composition; and The coating composition is applied to the surface of a metal substrate to form a film layer, and then sintered for the second time to form the coating layer.
7. The method for preparing the coating according to claim 6, characterized in that: The first sintering temperature is 1000°C to 1400°C and the time is 10min to 60min; and / or The grinding includes ball milling, the rotation speed of the ball mill is 200-400 r / min, and the time is 5-24 hours.
8. The method for preparing the coating according to claim 6, characterized in that: The second sintering temperature is 600°C to 900°C and the time is 20min to 60min; and / or The coating is carried out by spraying, the spraying pressure is 0.3-0.6Mpa, and the spraying distance is 15-45cm.
9. The method for preparing the coating according to claim 6, characterized in that: The filler raw materials include: 30wt% to 90wt% silicon dioxide; 1wt% to 30wt% alumina; At least one of 0.3 wt% to 10 wt% boron oxide, 1 wt% to 20 wt% sodium oxide, and 1 wt% to 20 wt% potassium oxide; at least one of 1 wt% to 10 wt% calcium oxide, 1 wt% to 10 wt% magnesium oxide, and 1 wt% to 10 wt% zirconium oxide; and At least one of 1wt% to 15wt% nickel oxide and 1wt% to 15wt% cobalt oxide; The step of forming the coating composition further includes: Add 1wt% to 10wt% of dispersant and 1wt% to 10wt% of film-forming agent, Wherein, the dispersant includes at least one of sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate; the film-forming agent includes at least one of sodium carboxymethyl cellulose, microcrystalline cellulose and hydroxypropyl cellulose.
10. A coating device, characterized in that: The invention comprises a heating device and a metal component arranged in the heating device, wherein the metal component has a coating, and the coating is the coating according to claim 5 or a coating obtained by the coating preparation method according to any one of claims 6 to 9.
Citation Information
Patent Citations
Ceramic coating with high-temperature resistance and wear resistance and preparation method of ceramic coating
CN106007678A
Acid-resistant and heat-resistant inorganic anticorrosive coating and preparation method thereof
CN111074276A
Inorganic-organic film and starting liquid composition therefor and method for preparation thereof, and applications and method for preparing them
WO2000068330A1
Cited By
Multi-element oxide ceramic coating refractory brick material containing reinforcement phase and preparation method thereof
CN121470993A